The Complex Link between Apoptosis and Autophagy: a Promising New Role for RB - JOÃO M.A. DELOU; DEBORAH BIASOLI; HELENA L. BORGES (Anais da Academia Brasileira de Ciências)
ABSTRACT Physiological processes, as autophagy, proliferation and apoptosis are affected during carcinogenesis. Restoring cellular sensitivity to apoptotic stimuli, such as the antineoplastic cocktails, has been explored as a strategy to eliminate cancer cells. Autophagy, a physiological process of recycling organelles and macromolecules can be deviated from homeostasis to support cancer cells survival, proliferation, escape from apoptosis, and therapy resistance. The relationship between autophagy and apoptosis is complex and many stimuli can induce both processes. Most chemotherapeutic agents induce autophagy and it is not clear whether and how this chemotherapy-induced autophagy might contribute to resistance to apoptosis. Here, we review current strategies to sensitize cancer cells by interfering with autophagy. Moreover, we discuss a new link between autophagy and apoptosis: the tumor suppressor retinoblastoma protein (RB). Inactivation of RB is one of the earliest and more frequent hallmarks of cancer transformation, known to control cell cycle progression and apoptosis. Therefore, understanding RB functions in controlling cell fate is essential for an effective translation of RB status in cancer samples to the clinical outcome.